2020
DOI: 10.21203/rs.3.rs-21644/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Negative impacts of excessive nitrogen fertilization on the abundance and diversity of diazotrophs in black soil with monocropping maize

Abstract: Background: Excessive nitrogen fertilizer input and low nitrogen fertilizer use efficiency in maize in China are serious ecological and economic problems, which might affect the procedures in the nitrogen cycle. To reveal the effects of long-term excessive nitrogen fertilization on diazotrophs in maize rhizosphere and bulk soil, we performed a long-term (five-year) N-input experiment (N rates from 0 to 300 kg N ha -1 ) in black soil maize in northeast China. The effect of N fertilizer application rates on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…A series of genes/gene clusters in Bacillus velezensis F21 associated with plant growth promotion including siderophore synthesis, production of growth-promoting, volatile organic compounds and growth-promoting hormones, and nutrition utilization was identified [20,123,247]. The siderophore bacillibactin favors plant growth and contributes to protect plants against pathogenic infections by complexing iron and making iron less available to pathogens.…”
Section: Genetics Of Plant Growth Promotion By Endophytic Siderophoreproducing Bacteriamentioning
confidence: 99%
“…A series of genes/gene clusters in Bacillus velezensis F21 associated with plant growth promotion including siderophore synthesis, production of growth-promoting, volatile organic compounds and growth-promoting hormones, and nutrition utilization was identified [20,123,247]. The siderophore bacillibactin favors plant growth and contributes to protect plants against pathogenic infections by complexing iron and making iron less available to pathogens.…”
Section: Genetics Of Plant Growth Promotion By Endophytic Siderophoreproducing Bacteriamentioning
confidence: 99%
“…Beneficial root‐associated microbes have positive effects on plant growth through enhancing nutrient availability, phytohormone biosynthesis, and protecting plants from biotic or abiotic stresses (Bakker et al, 2018; Hu et al, 2022; Xiong & Lu, 2022). Studies have shown that root‐associated microbiota are affected by biotic and abiotic factors, such as plant genotype, developmental stage, and nutrient status (Bakker et al, 2018; Bulgarelli et al, 2013; Chen, Hao, et al, 2021; Chen, Li, et al, 2021). However, the underlying relationship between root‐associated microbiota and maize NUE in the context of rhizosphere metabolites is largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In modern breeding, maize is typically grown under high N input conditions (Moose & Below, 2009; Wissuwa et al, 2009), which could result in the loss of some beneficial plant–microbe interactions relative to nutrient acquisition in maize during long‐term screening (Chen, Li, et al, 2021; Wissuwa et al, 2009). A previous study showed that rhizosphere microbiota recruited by recent germplasm have fewer functions in N provision and more functions in N losses (Favela et al, 2021).…”
Section: Introductionmentioning
confidence: 99%